DRUG TREATMENT OF PATIENTS WITH THE HISTORY OF ACUTE STROKE: DATA OF THE PILOT PHASE OF THE OUTPATIENT REGISTRY «REGION» - S. A. Boytsov; M. M. Loukianov; S. S. Yakushin; S. Yu. Martsevich; L. V. Stakhovskaya; A. N. Vorobyev; A. V. Zagrebelnyy; A. N. Kozminsky; K. A. Moseichuk; K. G. Pereverzeva; E. A. Pravkina; E. N. Belova; et al. (Столичная издательская компания, 2017)
Aim. To study the pharmacological treatment of patients with acute stroke (AS) within the prospective outpatient registries.Material and methods. In the pilot phase of the study, conducting on the base of one of the out-patient clinic in Ryazan city, 200 and 115 patients were included into the outpatient registry of patients with AS history of any remoteness (AS-AR registry), and outpatient registry of the first apply (AS-FA registry) to the out-patient clinic after stroke, respectively. The correspondence of the prescribed and actually taken drug therapy to clinical recommendations, its continuity, and the adherence of patients to treatment were assessed during the prospective observation.Results. Most patients did not receive adequate therapy to reduce the risk of AS and other cardiovascular complications in the outpatient stage, especially in the period prior to the reference AS. Drugs with a proven beneficial effect on the prognosis in the post-stroke period were prescribed significantly (p and after 2 years - in the AS-FA registry, the frequency of the therapy was not significantly different from the frequency of prescribing at the stage of inclusion in the registers, with the exception of statins (they were taken 1.7 and 1.5 times less frequently). Prognostically significant prescriptions of the inclusion phase were performed in the long-term follow-up period in 49% and 70% of patients (on average 58%), respectively; however, the frequency of first-time therapy was 44% and 19% of the total number of prescriptions in this period, respectively. Adherence to treatment, according to the Morisky-Green questionnaire, was revealed in 17.7 and 51.7% of patients, respectivelyConclusion. The results of the pilot phase of the REGION study (AS-AR and AS-FA outpatient registries) showed that the quality of the prescribed drug therapy of patients in out-patient clinic is inadequate. A comparison of the data of AS-AR and AS-FA registries allows to make a preliminary conclusion that over the 5-year period separating the remoteness of AS development in these registries, the quality of patient treatment has significantly improved, although not enough. The proportion of previously performed prognostically significant prescriptions averaged only about 60% at the stage of the further prospective follow-up. In general, during the observation period, taking into account newly made prescriptions, the frequency of adequate drug therapy during the observation period decreased only for statins. Most patients were not sufficiently committed to pharmacological treatment according to the Morisky-Green questionnaire.